Productivity Assessment of Digging and Loading Equipment (Cat 330D2L) and Hauling Equipment (Fuso 220PS) in Coal Mining at PT. Bhumi Sriwijaya Perdana Coal, Musi Banyuasin Regency, South Sumatra - Prasetyo, Yoga Tri; Paradise, Mycelia; Mukarrom, Faisol (MO.RI Publishing, 2024)
PT. Bhumi Sriwijaya Perdana Coal, a coal mining company located in Musi Banyuasin District, South Sumatra, utilizes Caterpillar 330D2L excavators and Mitsubishi Fuso 220PS dump trucks for coal extraction activities. The company set a production target of 52,612 tons/month for March 2023. However, actual production fell short, with the hauling equipment achieving only 41,260.08 tons/month, despite the loading equipment exceeding the target with 59,086.93 tons/month. This research aims to identify factors hindering the achievement of production targets and propose strategies for improvement. The analysis revealed that the mismatch between the loader and hauler operations, reflected by a low match factor of 0.57, was a significant contributor to inefficiencies. Additional challenges included extended cycle times influenced by front-loading patterns, hauling path conditions, and equipment synchronization. After implementing improvements, including cycle time optimization and increased loading flow, the productivity of the Mitsubishi Fuso 220PS dump trucks increased to 59,732.67 tons/month. The match factor between the Caterpillar 330D2L and the Mitsubishi Fuso 220PS improved to 0.83, demonstrating enhanced operational alignment. These findings highlight the importance of addressing cycle times, optimizing equipment compatibility, and improving workflows to meet production targets effectively.